CHARACTERISTICS OF RUMEN FERMENTATION WITH FEED FORMULATION USING MOLASSES IN-VITRO - Sari, Y. M.; Mega Sari, Rica; Nurhaita, Nurhaita; Surtina, Dara; Astuti, Tri (Department of Agriculture, 2024)
This study aims to determine the effect of molasses use in ruminant livestock rations on rumen fluid characteristics in vitro. This study was conducted using a Completely Randomized Design experimental method with 3 treatments and 5 replications, the treatments consisted of: P0 = Ration formulation without molasses use, P1 = Ration formulation with 3% molasses use, P2 = Ration formulation with 6% molasses use. The variables observed were pH value, NH3 production and rumen fluid VFA production. The results of the study for pH value obtained P0 = 6.98; P1 = 6.94; P2 = 6.89. NH3 production P0 = 10.02 mg / 100ml; P1 = 10.89 mg / 100ml; P2 = 11.42 mg / 100ml and VFA production P0 = 104.00 mM; P1 = 120.00 mM; P2 = 130.00 mM. Based on the results of the study, it was shown that the use of molasses in the ruminant livestock ration formula had no significant effect (P>0.05) on the pH, and had a significant effect (P<0.05) on the production of NH3 and VFA in the rumen in vitro. Where the use of molasses up to 6% in the ration formulation can increase NH3 production, VFA production and maintain the pH value of the rumen fluid.